Elucidation of Diversity among Psidium Species using Morphological and SPAR methods - Thomas, Abin Mani*, Rachana Mishra and George (Journal of Phytology, 2011)
Molecular marker assisted characterization is lacking in Psidium genus. This study focuses on the genetic variability among eleven Psidium species by employing morphological and SPAR (RAPD and ISSR) methods. Morphological characterization was done based on parameters such as size, shape, foliage characters and habit of the plant specimens. In SPAR methods, 16 RAPD and 31 ISSR primers were used to distinguish the genetic variability. 3 RAPD and 4 ISSR primers showed 100% polymorphism, while average polymorphism in both marker systems was 77% and 81.6% respectively and the cluster analysis showed a more or less similar pattern. Dendrograms revealed two main clusters, separating the genus, F. sellowiana and Psidium sp. with a genetic distance of 0.86.